(untitled) (Bioagro, 2022)
Tomato is one of the most consumed vegetables, with abundant pests and diseases problems limiting its production. This research had two objectives: in the first one, the morphological characteristics of five different tomato populations, were described; in the second, the yield response of candidate-to-be varieties genotypes was evaluated when submitted to chemical or biological control of pest and diseases that commonly attack the crop. The populations showed distinctive morphological characteristics, fruit firmness, size, and shape. The experimental test results indicated significant differences among varieties and in the interaction of variety x method of control. The control variety showed the lowest yield (28,630 kg·ha-1) when compared to the candidate varieties, especially Variety 2 (66,090 kg·ha-1). Variety 2 (cherry-size-fruit) and Variety 3 (large-size-fruit) should be taken into consideration for large-scale cultivation due to their high yield. Varieties 2 and 3 reacted adequately to both kind of pesticides, with an advantage in yield under chemical control. Nonetheless, the use of chemical products was minimal (3-4 applications were enough), as compared to the high number of applications that are currently used under the traditional tomato cultivation in Ecuador.